Effect of inlet temperature in pineapple and Centella asiatica L. Spray drying: article - Mohd Rahimi, Mohamad Ridzuwan; Abd Hashib, Syafiza (2019)
Spray drying is one of the method to convert fruit juice into powder form to improve shelf life and easy transportation but it tend to become sticky due to high sugar content especially in Moris pineapple. The effect of addition of CAL with maltodextrin as carrier agent and inlet air temperature towards physicochemical of pineapple powder were studied. The spray dryer model used was a laboratory scale dryer and samples were run at different inlet temperatures of 130°C, 150°C, and 170°C. Maltodextrin was used as a carrier agent at different concentrations of 20%, 30% and 40% (w/v) while CAL at 5%, 10% and 15% (v/v) respectively. The pineapple powder were then analyzed for pH, sugar levels, moisture content, bulk density, antioxidant activity, product yield and colour. pH powder slightly increased from 3.80-3.96 to 3.81-4.02. Sugar level decreased significantly after spray drying from 19.0-29.9°Brix to 6.69.7°Brix. At higher inlet temperatures and increment of maltodextrin content, the moisture content of pineapple powder decreased from 6.03-6.12% to 5.28-5.48%. The highest bulk density is 0.58 g/ml at 130°C and 40% concentration. Product yield increased with increasing of inlet temperature from 5.57% to 8.89%. The colour of powder produced is light green yellowish affected by CAL juice. The antioxidant activity showed best at 130°C where it obtained positive value. As a conclusion, the best condition of spray drying to be at 170°C and 40% maltodextrin concentration due to its low moisture content, high bulk density and product yield. The addition of CAL also does affect the physicochemical properties due to it contain high moisture content, dark green in colour, pH value at 5.5 and high antioxidant level